"In the beginning God created the heavens and the earth": What do science and faith have to do with youth ministry? - Weber, Shantelle (HTS teologiese studies, 2021)
Dating back to medieval times, and some would contend even ancient biblical times, scholars of the faith have made significant contributions to scientific discovery. Theology was considered foundational to the understanding of our natural world, and possibly the motivation for scientific enquiry. No tension existed between observation and study of the natural world and faith. In modern times the rift between science and faith, from a conservative evangelical perspective, has been ever-widening with both sides viewing the other with growing suspicion. This article reflected on the impact that this approach to science and faith has had on the faith formation of youth raised within evangelical faith communities. It investigated how conservative evangelical teachings concerning the creation story has hindered the faith formation of youth in this context. We connected this tension between science and faith as we considered connections to environmental justice as it related to youth in marginalised communities in South Africa. This article served as an introductory exploration of why we believe young people are not engaging with environmental issues.Contribution: As part of the special edition on youth, faith and climate change, this article reflects on the impact that the conflicted evangelical approaches to science and faith have on the faith formation of youth raised within evangelical faith communities. It investigates how fundamentalistic evangelical teachings concerning the creation story has hindered the faith formation of youth in this context. Within the context of environmental justice and inequality, this article highlights the need for church engagement on issues related to these conflicted approaches, its effect on how youth engage on issues affecting their environments, and youth ministry practice within evangelical churches.